PENGARUH MOTIVASI, BUDAYA ORGANISASI DAN KOMITMEN ORGANISASI TERHADAP KINERJA PERAWAT DI RSUD DR. MOEWARDI SURAKARTA - Efliani, Destria; Mustofa, Amin; Mardalis, Ahmad (Universitas Muhammadiyah Surakarta, 2015)
Providing health care to patients, hospitals greatly relies on the presence of a nurse. This makes the nurse as a reliable resource as the spearhead of hospital services to patients. Each activity hospitals, nurses also always had an important role. The nurses performance is one indicator of performance hospital as a service industry that always rests on the human resources of competence. Purpose of this research to determine the effect of motivation, organizational culture and organizational commitment to the nurses of performance at the Dr. Moewardi General Hospital in Surakarta. The research method of multiple linear regression with simple random sampling technique. The population is a nurse in the Emergency Ward, Mawar Ward I, II and Melati Ward I, II , III, at Dr. Moewardi General Hospital in Surakarta as many as 100 people. There was effect motivation, organizational culture and commitment organizational to the nurses of performance at Dr. Moewardi General Hospital in Surakarta with P-value of 0.001 and r of 0.52.